1978
DOI: 10.1136/thx.33.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory effects of aerosol gentamicin.

Abstract: Dally, M. B., Kurrle, S., and Breslin, A. B. X. (1978). Thorax, 33,[54][55][56] Seven subjects, all from the asthmatic group, developed at least one immediate FEV1 fall of 20% or more. The reactions ranged up to 71% and occurred to both test solutions. There was a trend towards greater reactions to the vehicle. In two subjects pretreatment with salbutamol and sodium cromoglycate did not modify these reactions. In three of the seven, inhalation of 2 ml normal saline produced FEV1 falls of 25% to 30%, but these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…However, other studies using aerosolized aminoglycosides have failed to define a benefit (17). Additionally, aerosolized antibiotics may be associated with significant bronchospasm (especially in patients with asthma), and locally administered agents may result in higher rates of resistant organisms (2,8).…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies using aerosolized aminoglycosides have failed to define a benefit (17). Additionally, aerosolized antibiotics may be associated with significant bronchospasm (especially in patients with asthma), and locally administered agents may result in higher rates of resistant organisms (2,8).…”
Section: Resultsmentioning
confidence: 99%
“…17,[45][46][47][48] As a result of the inability of aerosol administration to deliver medication to areas of the lungs that are not ventilated, the administration of antimicrobials by inhalation alone is not appropriate when substantial consolidation or parenchymal involvement is evident, but it may be of benefit as an adjunct to oral or parenteral administration. [50][51][52] Bronchial constriction resulting from aerosol administration of aminoglycoside solutions can, however, be attenuated by prior treatment with a β 2 -adrenergic agonist. 8 There are several reports that document the alteration of pulmonary mechanics in humans following aerosol administration of antimicrobials, primarily as the result of bronchoconstriction, and it has been suggested that this is the result of irritation induced by the drug, the drug carrier, or the tonicity of the solution.…”
Section: Discussionmentioning
confidence: 99%
“…47,49 Aminoglycoside and β-lactam antimicrobials may be inactivated in bronchial secretions, but it is likely that this can be overcome by administration of high concentrations of these antimicrobials. 51,53 Serum concentrations of gentamicin following aerosol administration are primarily the result of pulmonary absorption. [50][51][52] Bronchial constriction resulting from aerosol administration of aminoglycoside solutions can, however, be attenuated by prior treatment with a β 2 -adrenergic agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a sulphitefree form of tobramycin was not commercially available in France. All other aminoglycosides, but not the commercially available form of amikacin in France (Amiklin1), contain sulphites that may be responsible for severe allergic side effects [14]. This is particularly important in CF patients who are known to have frequent bronchial hyperreactivity [15] and are at risk of bronchial allergy [16], and this is why the present study was conducted with amikacin.…”
Section: Discussionmentioning
confidence: 99%